SUN-001 Identification of Dehydroepiandrosterone-s (DHEA-s) Elevation Due to Performance Enhancing Supplements - Shin, Terry (J Endocr Soc, 2020)
Background: Recreational athletes and individuals in certain occupations may utilize supplements with the goal of enhancing their physical performance and strength. These individuals may be reluctant to provide their supplement use history due to the stigma associated with performance enhancing drugs. We report a case of supplement use causing elevated dehydroepiandrosterone sulfate (DHEA-S) levels in a young woman presenting with alopecia. Clinical Case: A 29-year-old Caucasian woman presented for evaluation of progressive alopecia spanning 7 years. She was initially managed by dermatology with topical ketoconazole and clobetasol creams followed by intra-lesional triamcinolone injections. Despite treatment, she had minimal improvement. She reported menarche at age 15 with normal regular monthly menstrual cycles and normal breast development. She has no significant medical history. Physical exam was unremarkable other than localized alopecia and athletic build. She denied any medication use. Routine laboratory screening showed a DHEA-S of 624 ug/dL (ref. 35-430) with repeat DHEA-S at 602.2 ug/dL. Complete blood count, metabolic panel, thyroid function test, total/free testosterone, estradiol, 17-hydroxprogesterone, urinary 17-ketosteroids, prolactin, and iron panel were all within normal limits. Anabolic abuse screen was negative. Adrenal imaging was normal. After discussion on elevated DHEA-S results, patient revealed that she was taking a supplement that contained enobosarm (Ostarine). She was instructed to discontinue the supplement and repeat her labs but she was lost to follow up. Discussion: Developed in 1997, enobosarm is a selective androgen receptor modulator (SARMs) that is increasingly used as a performance-enhancing drug. SARMs have tissue specific androgenic receptor effect and patients on SARMs can present with a completely normal hypothalamic-pituitary gonadal axis without biochemical evidence of hyperandrogenism; which was the case in our patient. Conventional anabolic drug abuse screens do not detect SARMs. There have been multiple studies that have evaluated different performance enhancing supplements and nearly 25% of tested products contained compounds that were not correctly labeled. It is therefore uncertain what may have raised this patient’s DHEA-S levels, but the authors theorize the supplement may have contained exogenous DHEA rather than a direct effect of enobosarm. Unfortunately, there is paucity of data or literature on the effect of SARMs on androgen hormone synthesis and DHEA-S levels. A PubMed search for SARMs and DHEA-S levels led to zero returns. It is important for clinicians to recognize and identify the possibility of SARM or supplement use in order to guide diagnostic and management decisions. Further investigation is needed to understand the impact of SARMs on laboratory data and its long term effects.